Penerapan Pidana Terhadap Terdakwa Tindak Pidana Menambang Terumbu Karang di Kawasan Konservasi - Putra Feli, Aidil; Fitriati, Fitriati; A. Kana, Philips (UNES Law Review, 2023)
Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands, explicitly explains criminal sanctions for perpetrators of mining coral reefs. This research is Normative Juridical legal research. Criminal Application Against Defendant Mining Coral Reefs in Conservation Areas In Decision Number 73/Pid.B/2017/PN Sit the defendant was charged under Article 73 paragraph (1) letter a of Republic of Indonesia Law No. 27 of 2007 concerning Management of Coastal Areas and Small Islands. Decision Number 592/Pid.Sus/2019/PN Pdg defendant Risal Bin Olleng was proven to have jointly committed the criminal act of destroying coral reef ecosystems in a conservation area as well as defendant I. Usmanto PGL. Brother and defendant II. Muhammad Nur PGL. The act mentioned above has been legally and convincingly proven guilty of committing the criminal act of "participating in committing acts which result in pollution and/or damage to fish resources and/or the environment in the fisheries management area of the Republic of Indonesia." The judge's consideration in imposing a crime on the defendant in Decision Number 73/Pid.B/2017/PN Sit and Number 592/Pid.Sus/2019/PN Pdg is that it has the same elements of consideration, namely each person, and the element of deliberately mining coral reefs, taking coral reefs in Conservation Areas, using explosives and toxic materials, and/or other methods that result in damage to the coral reef ecosystem.